DIFFERENCES IN POSTPARTUM MATERNAL DEPRESSION LEVELS BASED ON CHARACTERISTICS OF MATERNAL AGE AND HUSBAND SUPPORT - Tisandra Safira Handini; Nunik Puspitasari (Universitas Airlangga, 2021)
The International Statistical Classification of Disease (ICD-10) defines postpartum depression as a mental and behavioral disorder that occurs after six-week labor. The number of postpartum blues in Asia is high and varies between 26-85%. In Indonesia, especially Jakarta, Yogyakarta, and Surabaya, the prevalence of postpartum depression is 11-20%. In Surabaya, 22% mothers had postnatal depression in 2003. The occurrence of postpartum depression is influenced by several factors namely biological and characteristic. This study aimed to analyze differences in postpartum maternal depression levels based on characteristics of maternal age and husband support. This study used quantitative with cross sectional study design. The population of this study was 209 mothers with postpartum depression in the timeframe of 6 weeks to 1 year. The sample size was 70 samples selected through simple random sampling. The retrieval of data was through surveys and questionnaires. The results of the study showed most respondents aged 26-30 years had high husband support and were not at risk of depression. There was a significant difference between postpartum maternal depression levels based on maternal age (p = 0.014) as well as on husband support (p = 0.000). Based on the results, researchers suggest to establish continuous husband support, conduct early detection, and educate mothers.Keywords: depression level, husband support, mother's age, postpartum depression